Genome-wide identification and characterization of Fur-binding sites in the cyanobacteria Synechocystis sp. PCC 6803 and PCC 6714. (21st October 2021) - Riediger, Matthias; Hernández-Prieto, Miguel A; Song, Kuo; Hess, Wolfgang R; Futschik, Matthias E
Abstract: The Ferric uptake regulator (Fur) is crucial to both pathogenic and non-pathogenic bacteria for the maintenance of iron homeostasis as well as the defence against reactive oxygen species. Based on datasets from the genome-wide mapping of transcriptional start sites and transcriptome data, we identified a high confidence regulon controlled by Fur for the model cyanobacterium Synechocystis sp. PCC 6803 and its close relative, strain 6714, based on the conserved strong iron starvation response and Fur-binding site occurrence. This regulon comprises 33 protein-coding genes and the sRNA IsaR1 that are under the control of 16 or 14 individual promoters in strains 6803 and 6714, respectively. The associated gene functions are mostly restricted to transporters and enzymes involved in the uptake and storage of iron ions, with few exceptions or unknown functional relevance. Within the isiABC operon, we identified a previously neglected gene encoding a small cysteine-rich protein, which we suggest calling, IsiE. The regulation of iron uptake, storage, and utilization ultimately results from the interplay between the Fur regulon, several other transcription factors, the FtsH3 protease, and the sRNA IsaR1.